PARROT: A Pilot Study on the Open Access Provision of Particle-Discrete Tomographic Datasets. (April 2022) - Ditscherlein, Ralf; Furat, Orkun; Löwer, Erik; Mehnert, Raik; Trunk, Robin; Leißner, Thomas; Krause, Mathias J.; Schmidt, Volker; Peuker, Urs A.
Abstract: Abstract : In the present paper, as part of an interdisciplinary research project (Priority Programme SPP2045), we propose a possible way to design an open access archive for particle-discrete tomographic datasets: the PARROT database (https://parrot.tu-freiberg.de ). This archive is the result of a pilot study in the field of particle technology and three use cases are presented for illustrative purposes. Instead of providing a detailed instruction manual, we focus on the methodologies of such an archive. The presented use cases stem from our working group and are intended to demonstrate the advantage of using such an archive with concise and consistent data for potential and ongoing studies. Data and metadata merely serve as examples and need to be adapted for disciplines not concerned here. Since all datasets within the PARROT database and its source code are freely accessible, this study represents a starting point for similar projects.